Prosociality in personality disorders: status quo and research agenda - Hepp, Johanna; Niedtfeld, Inga (Current opinion in psychology, 2022)
Personality disorders (PDs) are characterized by interpersonal dysfunction and deficits in prosociality are theorized to contribute to this. We review studies linking categorical PDs to prosocial and antagonistic traits and highlight studies that assessed prosocial behavior in PDs via economic games. We structure our review based on the recently proposed affordance framework of prosocial behavior, summarizing the evidence for exploitation, reciprocity, temporal conflict, and dependence under uncertainty as situational affordances that allow the expression of personality in prosocial behavior. We conclude that some of the inconsistencies in the literature may be due to studies focusing on different situational affordances and the reliance on categorical PDs. We suggest a research agenda and a set of testable hypotheses based on maladaptive personality traits included in the newly implemented dimensional PD diagnoses in ICD-11 and DSM-5.